Etiology-independent activation of the LTβ-LTβR-RELB axis drives aggressiveness and predicts poor prognosis in HCC - Scherr, Anna-Lena; Nader, Luisa; Xu, Kaiyu; Elssner, Christin; Ridder, Dirk A.; Nichetti, Federico; Mastel, Manuel; Fritzsche, Sarah; Kelmendi, Eblina; Schmitt, Nathalie; Hoffmeister-Wittmann, Paula; Weiler, Sofia Maria Elisabeth; et al. (Hepatology, 2024)
Background and Aims: - HCC is the most common primary liver tumor, with an increasing incidence worldwide. HCC is a heterogeneous malignancy and usually develops in a chronically injured liver. The NF-κB signaling network consists of a canonical and a noncanonical branch. Activation of canonical NF-κB in HCC is documented. However, a functional and clinically relevant role of noncanonical NF-κB and its downstream effectors is not established. - Approach and Results: - Fur human HCC cohorts (total n = 1462) and 4 mouse HCC models were assessed for expression and localization of NF-κB signaling components and activating ligands. In vitro, NF-κB signaling, proliferation, and cell death were measured, proving a pro-proliferative role of v-rel avian reticuloendotheliosis viral oncogene homolog B (RELB) activated by means of NF-κB-inducing kinase. In vivo, lymphotoxin beta was identified as the predominant inducer of RELB activation. Importantly, hepatocyte-specific RELB knockout in a murine HCC model led to a lower incidence compared to controls and lower maximal tumor diameters. In silico, RELB activity and RELB-directed transcriptomics were validated on the The Cancer Genome Atlas HCC cohort using inferred protein activity and Gene Set Enrichment Analysis. In RELB-active HCC, pathways mediating proliferation were significantly activated. In contrast to v-rel avian reticuloendotheliosis viral oncogene homolog A, nuclear enrichment of noncanonical RELB expression identified patients with a poor prognosis in an etiology-independent manner. Moreover, RELB activation was associated with malignant features metastasis and recurrence. - Conclusions: - This study demonstrates a prognostically relevant, etiology-independent, and cross-species consistent activation of a lymphotoxin beta/LTβR/RELB axis in hepatocarcinogenesis. These observations may harbor broad implications for HCC, including possible clinical exploitation. Export
Gesehen am 19.02.2024